2020
DOI: 10.3390/nu12082184
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Pain

Abstract: In terms of antinociceptive action, the main mode of action of magnesium involves its antagonist action at the N-methyl-d-aspartate (NMDA) receptor, which prevents central sensitization and attenuates preexisting pain hypersensitivity. Given the pivotal function of NMDA receptors in pain transduction, magnesium has been investigated in a variety of pain conditions. The oral and parenteral administration of magnesium via the intravenous, intrathecal, or epidural route may alleviate pain and perioperative anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 118 publications
3
64
0
4
Order By: Relevance
“…Following absorption from the upper intestine, they can manage the muscle cells’ response to nerve stimuli through numerous functions [ 274 ]. Even though the tocolytic effect of magnesium has already been proven in vivo and in vitro, the best dosage for treating or preventing dysmenorrhea is not yet clear [ 275 ].…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…Following absorption from the upper intestine, they can manage the muscle cells’ response to nerve stimuli through numerous functions [ 274 ]. Even though the tocolytic effect of magnesium has already been proven in vivo and in vitro, the best dosage for treating or preventing dysmenorrhea is not yet clear [ 275 ].…”
Section: Menstrual Disordersmentioning
confidence: 99%
“…It was also demonstrated that hypermagnesemia reduced headshaking behavior in horses [19]. These actions of Mg have been attributed to its ability to block N-methyl-D-aspartate (NMDA) ionotropic receptors and voltage-dependent calcium channels, reducing neuronal excitability [1,2,21,22]. The inhibitory effect of Mg 2+ over NMDA receptor activity has also been the rationale for its use in acute brain injury, nociception, anesthesia, and behavioral disorders [1][2][3]19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of short-term hypermagnesemia on behavior, cardiovascular function, and neuromuscular activity in horses were recently documented [2,3,19], further demonstrating that Mg is a pleiotropic ion. Magnesium supplementation is recommended for a number of human disorders and is being promoted as a pre-anesthetic to reduce pain [21]. In addition, due to its calcium-channel and NMDA receptor blocking properties and prolonged half-life in horses, MgSO 4 supplementation should be considered for conditions associated with nociception, neuronal hyperexcitability, and energy dysregulation [1,2,21].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Nociplastic pain is generally chronic and widespread and is caused by disturbance of central pain processing mechanisms such as elevated excitability of ascending and descending pain facilitatory pathways and/or reduced inhibition of descending anti-nociceptive pathway [14,75,76]. The condition refers to central sensitization in which pain is elicited by innocuous stimuli or different kind of stimuli, resulting in causing central hyperalgesia or allodynia, respectively [77]. The process involves increased activity of the insula, anterior cingulate cortex, and the prefrontal cortex, which becomes active during acute pain sensation as well as of the brain stem nuclei, dorsolateral frontal cortex, and parietal cortex, which do not participate during acute pain sensation [78].…”
Section: Modulation and Nociplastic Painmentioning
confidence: 99%